Transfer, Validation and Application of HPLC Analytical Method for Simultaneous Determination of Paracetamol and Diclofenac in Tablets - Baruti, Emile Tweni; Kindenge, Jérémie Mbinze; Issa, Issa Yakusu; Amani, Marguerite Borive; Bankiantima, Elodie Nsasi; Kadima, Justin Ntokamunda; Djangeing’a, Roland Marini (International Journal For Research In Biology & Pharmacy, 2021)
Various pharmaceutical preparations containing paracetamol in combination with other nonsteroidal anti-inflammatory drugs are produced for the treatment of postoperative pain management. A lack of selective analytical techniques makes it difficult to fully assay all incorporatedactive ingredients. An original HPLC method developed at the University of Liège for the assay of the paracetamol-diclofenac combination in tabletshas been transferred and validated at the University of Kisangani for its application locally. The use of an Xbridge® column (C18, 100 x 4.6 mm/3.5µm) instead of Xbridge® (C18, 250 x 4.6mm/5µm) allowed to reduce the time of analysis from 60 min to 20 min, as well as the consumption of methanol in the mobile phase, while maintaining the efficiency and selectivity of the original method. After validation the method was applied for the analysis of two generics marked in the city. The tranferedmethod allows an appreciable saving in time and in the solvent economy to be applied in routine for quality control of generics in circulation.